A systematic literature review on the use of supercritical fluids for cleaner production in the textile industry - Ascencio-Ramirez, Christina (2020)
A systematic literature review sought to determine the potential of supercritical fluids in the textile industry to achieve cleaner production. To this end, a comprehensive analysis of various important research articles was carried out, taking as a basis those whose results were positive for the environment in terms of efficient use of resources. It was found that the technology that includes the use of supercritical fluids is the perfect substitute for those wet textile subprocesses within the dyeing industry that, by their nature, produce contaminated effluents and have a high-energy consumption.